Determination of the level of pedagogical formation students’ academic locus of control - Süleyman Can; Erdil Durukan (International Journal of Evaluation and Research in Education (IJERE), 2019)
Academic locus of control has an important place in explaining students’ behaviors in educational settings. The purpose of the current study is to determine the level of the pedagogical formation students’ academic locus of control and to investigate whether this level varies depending on some variables. The study employed the survey model, one of the quantitative research methods. The universe of the study is comprised of the students enrolled at the pedagogical formation program initiated in the fall term of 2015-2016 academic year in Muğla Sıtkı Koçman University and the sampling consists of 397 pedagogical formation students. As the data collection tool, the academic locus of control scale was used in the current study. It was concluded that the pedagogical formation students’ level of academic locus of control is medium. It was also found that the students’ academic locus of control, internal locus of control and external locus of control do not vary significantly depending on gender and department; yet, vary significantly depending on age. Furthermore, the pedagogical formation students’ level of satisfaction was found to be significantly correlated with the external locus of control but not with the internal locus of control and academic locus of control.